Value co‐creation in online healthcare communities: The impact of patients’ reference frames on cure and care - Oerle, Sarah; Lievens, Annouk; Mahr, Dominik (Psychology & marketing, 2018)
The gradual transition of health care toward businesses during the past 50 years has converted passive patients into active customers. In our digital society, patients increasingly use online health communities to satisfy complex needs that healthcare professionals leave unmet, including the creation of cure‐oriented (i.e., functional) and care‐oriented (i.e., emotion) value. This research investigates patients’ reference frames (self versus other) as an information processing mechanism and their impact on value creation in online communities. The analysis of 1,687 online postings of a leading healthcare platform shows that self‐referencing is typical for information obtained through an individualistic, patient–doctor encounter; other‐referencing emerges when patients focus on the needs of their peers. Information gathered through the patient–doctor encounter and processed with a self‐referencing frame accordingly enhances cure‐related value, but limits care‐oriented value co‐creation. Other‐referencing does exactly the opposite: it creates a barrier to cure‐related value, but stimulates care‐related value. A patient's experience with the community largely moderates the impact of both self‐ and other‐referencing on cure‐ and care‐related value. These findings show that online health communities can identify and address unmet patient needs, but healthcare professionals still play a critical role in terms of ensuring information quality in online health communities.